CONNOTATION CONCEPT IN THE LINGUISTIC DIMENSION - Гашибаязова, Олександра (Linguistic Bulletin (Movoznavchyi Visnyk), 2020)
This article underscores the importance of contextualizing the connotation within the linguistic dimension necessitated by the need to generalize the theoretical framework of the concept, to distinguish between broad and narrow meaning of the connotation, to characterize its meaningful content and to define its scope and limits. Based on the abovementioned core issues it is important to consider the adjective as one of the most connotatively colored parts of speech, determining the structure of the connotation components in the adjectives through the lens of language and speech system. Purpose. The aim of the article is to analyze the approaches used to define the term «connotation» through the adjective semantics. Methods. The research methods include analysis, synthesis, observation, definitive analysis, linguistic description of linguistic facts, and classification. Results. The current body of research is analyzed that allowed us to summarize the theoretical elaboration of connotation, to characterize the concept content, and to substantiate its optimal definition. When generalizing the approaches used to differentiate between a broad and a narrow meaning of the connotation, the synthesis of both approaches is underscored. The two types of the connotation – the usual (regular) and occasional (author’s) connotation are identified. The structure of the adjective connotation in language and communication is determined. In the language system, the adjective connotation structure is represented by three components including expressive, emotional and evaluative components, while in communication the adjective connotation structure includes four components namely expressive, emotional, evaluative and functional. Originality. The originality of the research lies in an attempt to summarize different approaches used to analyze the connotation, to substantiate the optimal definition of the connotation concept, and to determine the connotation structure of the adjectives in language and communication. Conclusion. It is concluded that the connotation is an additional semantic, emotional, pragmatic or stylistic shade of meaning that is of usual or occasional type, adds to word semantics and expresses an emotionally-evaluative attitude toward your subject. The connotation actively participates in the expressive-emotional-evaluative nomination; it also creates a new secondary meaning to the word in communication which is subsequently assimilated by language. The research prospect can be seen in explaining the ways in which the connotation is expressed in the adjective semantics.